On asymptotically lacunary statistical equivalent of order ?? of difference double sequences - Et, Mikail; Kandemir, Hacer Sengul; Cinar, Muhammed (Wiley, 2022)
In this article, we introduce and investigate the concepts of Delta theta m-asymptotically statistical equivalent of order alpha similar to and strong Delta theta m-asymptotically equivalent of order alpha similar to of double sequences. Also, we give some relationships related to these concepts.
Keywords: asymptotically statistical equivalent; difference double sequence; lacunary sequence